Migration Infrastructures in West Africa and Beyond - Kleist, Nauja; Bjarnesen, Jesper (Merian Institute for Advanced Studies in Africa (MIASA), 2019)
Infrastructure is becoming an influential field of inquiry across the social sciences as it has been in policy related research for some time. In migration and mobility related research, the recent introduction of the concept of “migration infrastructure” represents an attempt to theorise the infrastructural approach in relation to the multifaceted mediation of migration. This MIASA working paper considers the usefulness and limitations of the concept of migration infrastructures in understanding labour mobilities in various West African contexts. This juxtaposition of West African cases with the Asian examples that informed the articulation of the concept of migration infrastructures suggests that the framework holds potential for moving beyond migrant-centred analysis, while leaving some open questions regarding the role of migrant agency, the discrepancies between intentions and uses of (migration) infrastructures, the significance of culturally embedded migrant imaginaries, and the impact of global migration governance on national or regional regulatory frameworks.
Keywords: Imaginaries; Labour migration; Methodology; Migration infrastructure; Mobilities; West Africa